Pentingnya Spirit Pancasila Benteng Penahan Gempuran Artificial Intelligence Dalam Bisnis Dan Pendidikan Akuntansi - Murdiansyah, Isnan; Slamet; Hamdani; As’ady, Mustofa (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2025)
This research aims to analyze the implementation of the spirit and values of Pencasila in dealing with the negative impact of artificial intelligence on business and accounting education through internalizing the spirit and values of Pancasila in the curriculum and learning of accounting education. This research uses the doxique concept pioneered by Pierre Bourdieu as a unit of analysis to detect traces of the dominance of masculinity, the impact of artificial intelligence in accounting education, especially in the Auditing 1 course. The results of this research show that reconstruction in the Auditing 1 course is an alternative solution for internalizing and transferring the spirit and values of Pancasila in the learning model and accounting education curriculum